Biliary Tract Review and Recent Progress - Yan, Qiang; Pan, Zhiping (IntechOpen, 2023)
Biliary tract disease is a common digestive system disease worldwide that can present with mild clinical signs or be life-threatening. This book discusses the pathogenesis, diagnosis, and management of four common bile diseases: common bile duct stones (CBDS), choledochal cyst (CC), gallbladder cancer (GBCa), and bile duct injury (BDI).